Strategi Manuver Geoekonomi Indonesia dalam Merespons Dukungan Negara-Negara Pasifik Selatan atas Isu Kemerdekaan Papua - Rezya Agnesica Helena Sihaloho; Rusdi J Abbas; Silvia Dian Anggraeni (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2021)
The focus of the study in this research is the issue of the right to self-determination of Papua which has the support of countries in the South Pacific region. The Free Papua Movement (OPM) in Papua is motivated by differences in the history of integration, social and economic conditions between Indonesia and Papua. The support given by these countries for Papua has disturbed Indonesia's political sovereignty and national security conditions, so that the Indonesian government has responded with soft power. The response is in the form of an economic approach to Papua (internal) and South Pacific Countries (external). In discussing this research, the author uses a geoeconomic perspective with qualitative research methods, through data collection techniques from literature studies and various sources that are credible and relevant to the research. In addition, this research is also supported by primary data through interviews with parties who have the ability to discuss research problems.Keywords: geo-economics, Papua, self-determinations issues, South Pacific countries